Management of Patients with Gastroschisis Requiring Extracorporeal Membrane Oxygenation for Concurrent Respiratory Failure. Issue 9 (September 2016) - Lalani, Alykhan; Ham, P. Benson; Wise, Linda J.; Daniel, John M.; Walters, K. Christian; Pipkin, Walter L.; Stansfield, Brian; Hatley, Robyn M.; Bhatia, Jatinder
Treatment of gastroschisis often requires multiple surgical procedures to re-establish abdominal domain, reduce abdominal contents, and eventually close the abdominal wall. In patients who have concomitant respiratory failure requiring extracorporeal membrane oxygenation (ECMO), this process becomes further complicated. This situation is rare and only five such cases have been reported in the ECMO registry database. Management of three of the five patients along with results and implications for future care of similar patients is discussed here. Two patients had respiratory failure due to meconium aspiration syndrome and one patient had persistent acidosis as well as worsening pulmonary hypertension leading to the decision of ECMO. The abdominal contents were placed in a spring-loaded silastic silo while on ECMO and primary closure was performed three to six days after the decannulation. All three patients survived and are developmentally appropriate. We recommend avoiding aggressively reducing the abdominal contents and using a silo to conservatively reducing the gastroschisis while the patient is on ECMO therapy. Keeping the intra-abdominal pressure below 20 mm Hg can possibly reduce ECMO days and ventilator time and has been shown to decrease morbidity and mortality. Patients with gastroschisis and respiratory failure requiring ECMO can have good outcomes despite the complexity of required care.